Does rail transit access affect firm dynamics? Analysis of firm births and closures in Maryland, USA - Basheer Saeed; Hiroyuki Iseki (Journal of Transport and Land Use, 2023)
Firm birth and firm closure are two interrelated dynamics relevant to measuring economic growth, yet most studies focus on firm birth only. Public transportation infrastructure may facilitate firm birth, but it may also avert firm closure through improved accessibility that can consequently lead to increased local density hence agglomeration economies. This study analyzes firm births and firm closures using the National Establishment Time Series (NETS) panel data from Maryland from 1991 to 2009. By examining both birth and closure patterns, this study estimates the likelihood of firm retention for areas in proximity to passenger rail stations of multiple levels of maturity, while controlling for a number of potentially confounding factors.